Fontes de proteína e níveis de suplementação na recria intensiva de bovinos de corte em pastagens tropicais - Faria, Artur Carmanini de (2021)
Our objective was to evaluate forage production, animal performance, blood parameters on the use of different levels and sources of protein in the supplementation of beef cattle reared on pasture. The area was subdivided into 16 paddocks with an average size of 2.5 ha with trough and individual drinking fountains. The experiment was conducted in a completely randomized design with a 2 × 2 factorial arrangement. Factors included two protein sources (FP) (soybean meal and DDGS), and two supplement levels (NS) in the dry season (10 and 16 ,7g.kg-1 of body weight) in the water station (7 and 10 g.kg-1 of body weight), using 4 paddocks per treatment. Nellore calves with initial weight of 220 kg and average age of 10 months were used, the initial stocking rate was determined to reach a forage offer of 7%. Forage collection was carried out every 28 days in a total area of 0.68 m2 to evaluate the morphological characteristics of the forage, and forage samples in simulated grazing to evaluate the chemical composition. To assess animal performance, the mean weight of the tracer animals after 16h fasting of solids and liquids was considered, collecting blood samples from 3 test animals per paddock to assess the serum profile. The lowest NS in the rainy season favored the increase in the proportion of leaves, leaf:stem ratio and leaf volumetric density, with a reduction in leaf:stem during the dry period of the year in the highest NS. The change in FP in the supplement did not impact forage canopy characteristics (P>0.05). When evaluating the morphological characteristics of the forage, only the F:C ratio differed between the NS (P=0.033), being higher when the smallest NS during the dry period. The chemical composition of the forage showed the highest CP content (P=0.007) at the lowest NS, while for NDFcp the highest concentration was observed at the highest NS (P=0.003) during the dry period. Animals receiving the highest NS had the highest supplement intake (P<.001) and the lowest pasture intake (P<.001). The GMD did not differ for NS (P=0.112) or for FP (P=0.980), with an average of 0.970 kg BW.animal-1 .day.-1 . In the dry period, the nutritional strategy that used the highest NS obtained greater weight gain per day (P<.001), stocking rate (P=0.005) and productivity (P<.001), but during the rainy period there was no effect. of the NS for these variables. All serum compounds evaluated in both periods were within the range considered to be adequate for the animal category evaluated. The nutritional strategy associating the highest NS with the DDGS as FP showed the highest net profit, which was R$ 2,519.95.ha-1 . Nutritional strategies that combine a high level of supplementation with different sources of protein, enable the intensification of breeding, where the use of the association of the largest NS with the DDGS as FP can be used as a strategy in order to ensure the greatest economic return of the system.